Optimum Selection based on the Energy Capacity between Different Types of Renewable Sources using a Controller - Bandekas, D.; Vordos, N.; Tarchanidis, K.; Magafas, L.; Tsirigotis, G. (Elektronika ir Elektrotechnika, 2007)
The forthcoming end of the fossil fuel era combined with the increase of energy consumption and with the dramatic expansion of the environmental problems, are leading our society to the one way use of the renewable sources of energy. Furthermore, attention has to be drawn on the energy saving and rational use. Full description of system selecting optimal renewable energy source is given. A complete study of each renewable source of energy will proceed. The system comprises a wind generator, a row of photovoltaic panels and their batteries. Both energy sources are driven to the system’s inverter and the whole supervising is performed by a controller. Inverter’s functional description and optimum energy source selection algorithm is presented. Ill. 7, bibl. 4 (in English; summaries in English, Russian and Lithuanian).